The Fungal Pathogen Candida albicans Promotes Bladder Colonization of Group B Streptococcus - Shing, Samuel R.; Ramos, Anissa R.; Patras, Kathryn A.; Riestra, Angelica M.; McCabe, Sinead; Nizet, Victor; Coady, Alison (Frontiers in Cellular and Infection Microbiology, 2020)
Group B Streptococcus (GBS) is a common cause of bacterial urinary tract infections (UTI) in susceptible populations, including pregnant women and the elderly. However, the factors that govern GBS persistence and disease severity in this niche are not fully understood. Here, we report that the presence of the fungus Candida albicans, a common urogenital colonizer, can promote GBS UTI. Co-inoculation of GBS with C. albicans increased bacterial adherence to bladder epithelium and promoted GBS colonization in vivo in a C. albicans adhesin-dependent manner. This study demonstrates that fungal colonization of the urogenital tract may be an important determinant of bacterial pathogenesis during UTI.